La costellazione dei generi: forme letterarie e modi del discorso nel pensiero di Paul Ricœur (ENTHYMEMA, 2013)
Ricœur’s philosophy developed through a constant and fruitful dialogue with a whole range of both ancient and modern literature. An overview of Ricœur ‘s works and of his major commentators, this paper reconstructs the connections between philosophy and literary genres: the latter offer Ricœur  the possibility to ‘consider more’ ethical issues in philosophy.